Seasonal variation in 25-hydroxyvitamin D concentrations in the cardiovascular health study. - Shoben, Abigail B; Kestenbaum, Bryan; Levin, Gregory; Hoofnagle, Andrew N; Psaty, Bruce M; Siscovick, David S; de Boer, Ian H (Am J Epidemiol, 2011)
Low circulating concentrations of 25-hydroxyvitamin D (25(OH)D) are associated with adverse health outcomes in diverse populations. However, 25(OH)D concentrations vary seasonally with varying exposure to sunlight, so single measurements may poorly reflect long-term 25(OH)D exposure. The authors investigated cyclical trends in average serum 25(OH)D concentrations among 2,298 individuals enrolled in the Cardiovascular Health Study of community-based older adults (1992-1993). A sinusoidal model closely approximated observed 25(OH)D concentrations and fit the data significantly better than did a mean model (P < 0.0001). The mean annual 25(OH)D concentration was 25.1 ng/mL (95% confidence interval: 24.7, 25.5), and the mean peak-trough difference was 9.6 ng/mL (95% confidence interval: 8.5, 10.7). Male sex, higher latitude of study site, and greater physical activity levels were associated with larger peak-trough difference in 25(OH)D concentration (each P < 0.05). Serum concentrations of intact parathyroid hormone and bone-specific alkaline phosphatase also varied in a sinusoidal fashion (P < 0.0001), inversely to 25(OH)D. In conclusion, serum 25(OH)D varies in a sinusoidal manner, with large seasonal differences relative to mean concentration and laboratory evidence of biologic sequelae. Single 25(OH)D measurements might not capture overall vitamin D status, and the extent of misclassification could vary by demographic and behavioral factors. Accounting for collection time may reduce bias in research studies and improve decision-making in clinical care.
Keywords: Aged; Biomarkers; Continental Population Groups; Exercise; Female; Humans; Male; Residence Characteristics; Seasons; Sex Factors; Vitamin D